Clitoria Ternatea Antioxidant Reduces Serum MDA in Leprosy Patients with Reversal Reactions - Fitri Aulia Ananda; Novi Kusumaningrum; Muflihatul Muniroh; Farmaditya EP Mundhofir; Renni Yuniati (Jurnal Ilmiah Kesehatan (JIKA), 2023)
Leprosy reaction type 1 or reversal reaction is a clinical condition in leprosy patients that can occur when the patient receives MDT treatment. Patients with a reversal reaction have high MDA levels due to oxidative stress caused by inflammation and bacterial activity. The aim of this study was to determine the effectiveness of the antioxidant C. ternatea in reducing serum MDA of leprosy patients with reversal reaction. The research method used an experimental study with a randomized single blind controlled trial design to compare 2 groups (11 subjects each). Group 1 was the control group which was only given standard prednisolone therapy. Group 2 is the treatment group that was given standard therapy plus adjuvant C. ternatea flower extract 2gr/day for 1 month. Blood sampling was carried out before and after treatment in each group to test MDA levels using the ELISA method. Statistical analysis of differences in MDA levels used the Mann Whitnet test. The difference in pretest-posttest MDA levels in the control group had a median of 0,33 pg/ml (-0,05-1,55) pg/ml, while the difference in pretest-posttest MDA levels in the treatment group was 0,89 pg/ml (0,55-4,44) pg/ml with a value of p=0,020 (p-value<0,05). The difference in pretest-posttest MDA levels in the treatment group was higher than the control group. This shows that standard therapy and adjuvant C. ternatea extract are more effective in reducing MDA levels in patients with type 1 leprosy reaction than just standard therapy.